Stigma, problem drug use, and welfare state encounters: changing contours of stigmatization in the era of social investment. (4th July 2019) - Andersen, Ditte; Kessing, Malene Lue
Abstract: Aim: This study examined the ways in which citizens who have self-identified as having problem drug use experienced welfare state encounters in Denmark and considered the findings in the context of the social investment paradigm. Methods: We conducted qualitative interviews with 106 Danish citizens who identified as having a problem drug use. The interviews were transcribed and coded in Nvivo to classify different types of welfare state encounters experiences. Results: Previous research has documented extensive prevalence of drug-related stigmatization in welfare state encounters; however, approximately two-thirds of the citizens in this study did not recount this kind of stigmatization as predominating. Three prevailing narratives were conveyed by these participants: (1) narratives describing encounters where welfare state authorities approached the participant as 'a whole person, ' (2) narratives depicting encounters where the participants were submissive, and (3) narratives about welfare state authorities who discredited the significance of the participants' drug problems and imposed expectations considered unrealistic by the participants, e.g. expectations related to labor market performance. In the third type of encounter, participants experienced incongruence between their actual and virtual identities; not because problem drug use was granted master status but because their self-identified severe drug problems were downplayed by the welfare state authorities. Conclusion: Encountering welfare state authorities who downplayed the importance of drug problems gave rise to a form of stigmatization which we conceptualize as 'neo-stigmatization' to emphasize the contrast to drug related stigmatization where the importance of drug use is elevated to the point of master status. Neo-stigmatization emerges as politically productive in the context of the social investment paradigm that increasingly ties social worth to labor market value. Alleviating neo-stigmatization requires a political-economic framework that recognizes the value of citizens as not just workers but also caregivers and care receivers.